Effect of Saccharomyces Cerevisiae and Lactobacillus Plantarum in Growth of Fusarium sp. - N.N. Mahmood (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2016)
Saccharomyces cerevisiae filtrate showed inhibitory effect against Fusarium spp. when grow in a liquid medium (Sabouraud) with different concentrations (1, 3, 5) %. The higher inhibitory effect against fungus growth was (24.5) mm at (5%) in PDA medium compared with control (36.5) mm during the seventh day propagation. The filtrate of Lactobacillus plantarum isolate was mixed with the PDA medium ,which showed inhibitory effect against Fusarium spp. The concentrated filtrate( one fold) appcarcd a  higher effect against the same fungus compared with un concentrated filtrate one. Saceharomyces cerevisiae and Lactobacillus plantarum were grown in (GYE) liquid  medium for(24,48,72)hr. and resulted growth  filtrate were tested against Fusarium growth for (7) days, the results showed that the fungus stopped its growth stopped  after (48- 72) hr. of incubation.